(untitled) - Timbrell, John A. (London, 1985)
Leading textbook in biochemical toxicology. Addresses dose-response relationships; metabolism; toxic responses, and provides detailed examples to illustrate mechanisms of toxicity
Keywords: Độc tính sinh học,Biochemical toxicology,Poisons,Chất độc; Metabolism,Chuyển hóa